ANALISA LAPORAN KEUANGAN UNTUK MENGUKUR KINERJA PERUSAHAAN ( Studi Kasus PT Adhi Karya(Persero) Tbk ) - Gusna Fitri (JURNAL AKUNTANSI BARELANG, 2019)
Financial ratio analysis is a measuring tool used to measure the company's financial condition, and can assess the performance of companies in a given period. Results from the analysis of financial reports is very useful for the management in making decisions on the future. The financial ratio is basically the ratio of accounts contained in the balance sheet and profit and loss, and the comparative financial statements (balance sheet and profit and loss) from year to year, so it can be seen the development of the company from year to year in the management of the resources available to obtain profits. Analytical framework used is the analysis of financial statements using the measuring tool of analysis of liquidity ratios, leverage ratios, activity ratios, profitability ratios to evaluate and measure the performance of the company. From the analysis of the financial statements of PT Adhi Karya (Persero) tbk after research showed that the condition of PT Adhi Karya (Persero) Tbk is Good. Although profit is still relatively small but quite stable and the company did not suffer losses in its operations.